Occupational exposures to disinfectants and pre-diabetes status among active nurses in Cyprus - Savi Ioannou; Solon Ioannou; Xanthi D Andrianou; Pantelis Charisiadis; Costas A Christophi; George Yiasoumi; Konstantinos C Makris (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: A cross-sectional study was designed in two hospitals of Cyprus to: (i) examine the possible association between exposure to disinfectants/trihalomethanes (THM) with point of care glycosylated hemoglobin (HbA1c) levels among active nurses, and (ii) identify the main determinants of pre-diabetes metabolic risk among active nurses in Cyprus. METHODS: In total, 179 nurses from two public hospitals in Cyprus were recruited excluding pregnant or nurses working <5 years (participation rate ~25.6%). End-of-shift urine samples were used to measure exposures to THM, and questionnaire items were used to construct improved exposure classification matrices, ie, the job exposure matrix (JEM) and the job-task exposure matrix (JTEM). RESULTS: Results showed associations between JEM- and JTEM-derived metrics of exposure and HbA1c for few disinfectants (eg, peracetic acid), but no consistent trends were derived. In multivariable models, adjusted for age, BMI, sex, smoking status and alcohol consumption, the number of night shifts per month, and (ln)chloroform (a THM compound) were associated with HbA1c levels [β 0.11 (95% confidence interval (CI) 0.05-0.17) and 0.05 (95% CI 0.00-0.11), respectively]. CONCLUSION: A significant association between the number of monthly night shifts and HbA1c was observed, but no consistent associations were found between three exposure metrics of eleven different disinfectants, or urinary THM and point of care HbA1c levels in active nurses. Replication of the study findings in larger prospective sample is warranted. This is a novel occupational health dataset shedding light on the possible metabolic effects of exposures to disinfectants/by-products that have not been studied before.